Neuroarchitecture and Cognitive Well-being in Communal Workspaces: A Comparative Review for Sustainable Design - Viona Dwi Sartika; Yohannes Firzal; R. Lisa Suryani; Pedia Aldy; Mira Dharma Susilawaty (Program Studi Arsitektur, Fakultas Teknik, Universitas Riau, 2026)
The high prevalence of mental health issues in urban work environments, particularly among productive-age populations in Indonesia, highlights the need for architectural approaches that prioritize well-being and sustainability. This study aims to provide an evidence-based understanding of neuroarchitecture principles and their application in communal workspaces as a strategy for achieving sustainable design and social sustainability. The research employs a Systematic Literature Review (SLR) of peer-reviewed journals published within the last five years, supported by a comparative analysis of four international case studies: Amazon Spheres, Google EMEA Engineering Hub, Second Home Hollywood, and Mr. Green's Office.The findings identify three key aspects that contribute to cognitive well-being. First, the integration of biophilic elements, such as vegetation, natural light, and water features, supports stress reduction and mental restoration in line with the Biophilia Hypothesis, Stress Reduction Theory, and Attention Restoration Theory (ART). Second, sensory stimulation through color, texture, and acoustics enhances physical, emotional, and intellectual well-being, supported by the principles of neuroarchitecture and Supportive Environment Theory (SET). Third, adaptive spatial layouts that emphasize flexibility, communal spaces, and spatial clarity encourage user control, social interaction, and social sustainability. Overall, the study shows that applying neuroarchitecture principles through biophilic design, sensory optimization, and adaptive spatial planning can create supportive communal workspaces and help address mental health challenges in both global and Indonesian contexts.